Report of first isolation of the zoonotic Arcobacter species from swine fecal samples in Ecuador - Simaluiza, Rosa Janneth; Fernández, Jimmy; Fernández, Heriberto (Austral Journal of Veterinary Sciences, 2018)
Arcobacter butzleri, A. cryaerophilus, A. skirrowii and A. thereius are recognised as emerging zoonotic agents, recovered from animals and human beings. The information available about Arcobacter species in Latin America is scarce. Among domestic animals, swine are considered important reservoir and source of contamination of different Arcobacter species. This communication reports the first simultaneous isolation of the four zoonotic Arcobacter species in Ecuador. Preliminary identification was done by phenotypic characteristics and definitive species identification was made by multiplex PCR method. Further investigation about the prevalence, distribution, ecology and interactions with human beings of these species is required.